The Book of Portraiture - Anne-Laure Tissut (Sillages Critiques)
In The Book of Portraiture, Steve Tomasula further develops his exploration of the meaning of forms. Through its constitutive play on imitation –each chapter taking up a form of writing, in the larger sense of the term, and a genre specific to a given time–, The Book of Portraiture offers an original vision of innovation in art while questioning the notions of author and subject. A conception of culture and of our relation to it is conveyed through this expression of the contemporary emphasizing continuity in representations.